Given a Cobb Douglas

$Y_t = A (K_t^\alpha L_t^{1-\alpha}) $

$ K_{t+1} = sY_t + (1-\delta) K_t$

How do we get the multiplier on productivity to be equal to $ \frac{1}{1-\alpha}$? I understand that if productivity increases, output increases, thus we get more capital and thereby more output and so on. But I can't reach this multiplier.

My Attempt:

If have x increase in A, then $Y_t=(1+x)A (K_t^\alpha L_t^{1-\alpha}) $

That is an x increase in Y.

$ K_{t+1} = s(1+x)A (K_t^\alpha L_t^{1-\alpha}) + (1-\delta) K_t$

$Y_{t+1}=(1+x)A * K_{t+1}^\alpha *L_{t+1}^{1-\alpha} $ $Y_{t+1}= (1+x)A * (s(1+x)A (K_t^\alpha L_t^{1-\alpha}) + (1-\delta) K_t)^\alpha * L_{t+1}^{1-\alpha} $

I think the increase here should be $x * \alpha $ but I can't see it. so that for a unit increase in productivity i.e x=1; $\Delta Y = 1 + \alpha + \alpha^2 +... =\frac{1}{1-\alpha} $

Also in the steady state we have, $ Y = A^\frac{1}{1-\alpha} * \frac{s}{\delta}^\frac{\alpha}{1-\alpha} * L$ taking logs we have that percentage change in A increases Y by $\frac{1}{1-\alpha}$.

  • 1
    $\begingroup$ You should show any work you've already done in attempting to solve this question. $\endgroup$
    – user18
    Jan 27, 2019 at 2:30
  • $\begingroup$ @KennyLJ I updated with my attempt $\endgroup$
    – Fatima
    Jan 27, 2019 at 2:54

1 Answer 1


Let $y=Y/L$ and $k=K/L$ be the per-worker levels of output and capital. Observe that $y=Ak^\alpha$.

Steady state is given by: $$k^*=sy^*+(1-\delta)k^*,$$ or $$k^*=sA(k^*)^\alpha+(1-\delta)k^*.$$

Doing the algebra: $$k^*=\left(\frac{sA}{\delta}\right)^{\frac{1}{1-\alpha}}.$$

And: $$y^*=A\left(\frac{sA}{\delta}\right)^{\frac{\alpha}{1-\alpha}}=A^{\frac{1}{1-\alpha}}\left(\frac{s}{\delta}\right)^{\frac{\alpha}{1-\alpha}}.$$

I am not sure what is meant by the "multiplier on productivity". I would interpret this term to be the answer to the question, "Given a small unit change in $A$, what is the resultant change in $y^*$?" That is, the following expression: $$\frac{\partial y^*}{\partial A}=\frac{1}{1-\alpha}A^{\frac{\alpha}{1-\alpha}}\left(\frac{s}{\delta}\right)^{\frac{\alpha}{1-\alpha}}.$$

However, clearly, this does not correspond to your desired answer. So I suspect what is really meant is the elasticity of $y^*$ with respect to $A$: $$\frac{\partial y^*}{\partial A}\div \frac{y^*}{A}=\frac{1}{1-\alpha}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.